Climate moderates potential shifts in streamflow from changes in pinyon‐juniper woodland cover across the western U.S. Issue 20 (7th September 2017) - Niemeyer, Ryan J.; Link, Timothy E.; Heinse, Robert; Seyfried, Mark S.
Abstract: Pinyon‐juniper (PJ) cover has increased up to 10‐fold in many parts of the western U.S. in the last 140+ years. The impacts of these changes on streamflows are unclear and may vary depending on the intra‐annual distribution and amount of precipitation. Given the importance of streamflow in the western U.S., it is important to understand how shifts in PJ woodland cover may produce changes in streamflow across the region's diverse hydroclimates. To this end, we simulated the land surface water balance with contrasting woodland and grassland cover with the Hydrologiska Byråns Vattenbalansavdelning (HBV) model at a 4‐km resolution across the distribution of PJ woodlands in the western U.S. We used shifts in evapotranspiration (ET) between woodland and grassland cover as a proxy for potential changes in streamflows. Comparison of HBV model results with paired catchment studies indicated the model reasonably simulated annual decreases in ET with changes from woodland to grassland cover. For the northern and western ecoregions of the PJ distribution in the western U.S. where precipitation predominantly occurs in the winter, HBV simulated a 25 mm (37%) annual decrease in ET with conversion to grassland from woodland. Conversely, in southern ecoregions of PJ distribution with prominent summer monsoons, annual differences in ET were only 6 mm (19%). Our results suggest that only 29% of the PJ distribution, compared to an estimated 45% based on precipitation amount alone, has the potential for meaningful increases in streamflow with land cover change from woodland to grassland.